Social empowerment and participation of people with disabilities through NGO activities - Baranauskienė, Ingrida; Gerulaitis, Darius; Radzevičienė, Liuda (Social Welfare: Interdisciplinary Approach, 2011)
According to the approved Lifelong Learning Strategy (2004) by the Ministry of Education and Science, Ministers of Social Security and Labour, the country must strive to involve NGOs and social partners in the development of adult education. According to Rutkienė, Trepulė (2009), the lifelong learning paradigm covers all areas of human learning, provides opportunities for people to learn throughout their lives. It is very important for those who have not used or had no access to education for various reasons, departed from the job market etc. Lifelong Learning emphasizes the importance of both the EU and Lithuania in the context of education policy and practice of education (Teresevičienė, 2001).